EFISIENSI RUANG SIRKULASI TRUK SAMPAH MELALUI PENDEKATAN ARSITEKTUR REGENERATIF (STUDI KASUS: TEMPAT PENIMBUNAN SAMPAH RAWA BUAYA) - Ningrum, Vanesa Cristiya; Mustaram, Agnatasya Listianti (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
The development of cities and the dynamics of their residents' activities demand spatial planning that is responsive to social and environmental changes. In dense urban areas, there is often an overlap between residential functions and logistics activities, which poses unique challenges in managing circulation, comfort, and environmental health. In 2022, Jakarta generated more than 7,500 tons of waste daily, with most of it transported to the Bantargebang Final Disposal Site (TPA). Meanwhile, the problem of poorly managed waste accumulation is becoming an increasingly pressing environmental issue, particularly in urban areas such as Rawa Buaya, West Jakarta. The research site is an area where waste is dumped by recyclers without government involvement and an adequate management system. This has resulted in environmental pollution, decreased air quality, and disrupted the social life of local residents. This situation demonstrates the importance of spatial planning and logistics distribution system management that takes into account the social and physical conditions of informal areas. A regenerative architecture approach is used as a framework to understand the possibility of more holistic and contextual solutions, particularly in terms of distribution channel efficiency, spatial integration with community activities, and environmental sustainability. The findings of this study are expected to strengthen efforts to improve the quality of living space in dense urban areas through an understanding of integrated and adaptive circulation. Keywords: garbage; landfill; Rawa Buaya; regenerative architecture; truck circulation Abstrak Perkembangan kota dan dinamika aktivitas warganya menuntut perencanaan ruang yang responsif terhadap perubahan sosial dan lingkungan. Di kawasan urban padat, sering terjadi tumpang tindih antara fungsi permukiman dan aktivitas logistik, yang menimbulkan tantangan tersendiri dalam mengatur sirkulasi, kenyamanan, dan kesehatan lingkungan. Pada tahun 2022, Jakarta menghasilkan lebih dari 7.500 ton sampah setiap hari, dengan sebagian besar diangkut ke Tempat Pembuangan Akhir (TPA) Bantargebang. Sementara itu, permasalahan penumpukan sampah yang tidak dikelola dengan baik menjadi isu lingkungan yang semakin mendesak, terutama di kawasan urban seperti Rawa Buaya, Jakarta Barat. Tapak penelitian merupakan area penimbunan sampah oleh pelaku daur ulang tanpa keterlibatan pemerintah dan sistem pengelolaan yang memadai. Hal ini berdampak pada pencemaran lingkungan, penurunan kualitas udara, serta terganggunya kehidupan sosial warga sekitar. Kondisi ini menunjukkan pentingnya penataan ruang dan pengelolaan sistem distribusi logistik yang mempertimbangkan kondisi sosial dan fisik kawasan informal. Pendekatan arsitektur regeneratif digunakan sebagai kerangka untuk memahami kemungkinan solusi yang lebih holistik dan kontekstual, terutama dalam hal efisiensi jalur distribusi, integrasi ruang dengan aktivitas warga, dan keberlanjutan lingkungan. Temuan dalam studi ini diharapkan dapat memperkuat upaya perbaikan kualitas ruang hidup di kawasan padat kota melalui pemahaman sirkulasi yang terintegrasi dan adaptif.